Method for improving gain stability of microchannel plate based on ion exchange and microchannel plate

CN122889647APending Publication Date: 2026-10-09NORTH NIGHT VISION SCI&TECH (NANJING) RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610924917.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]目前,微通道板长时间工作电子倍增效率退化这一瓶颈技术问题导致超二代像增强器的合格率及稳定性不理想

Benefits of technology

[0019]在ALD沉积后的原位高温退火工艺,通过热活化驱动,使外源氧原子精确填补膜层内部及界面的氧空位缺陷,抑制了工作过程中的热电子发射与场致发射,降低暗电流与噪声,显著延长微通道板的工作寿命,提高MCP产品一致性和可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889647A_ABST
    Figure CN122889647A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of microchannel plates, and discloses a method for improving the gain stability of a microchannel plate based on ion exchange, which adopts the ion exchange method to immerse a glass substrate after hydrogen burning into a molten salt solution, K + , Na + on the surface of the channel and other cations in the molten salt are subjected to ion exchange, so that the K and Na concentrations on the inner wall surface of the channel are significantly reduced. After the MCP sample is treated through the special steps, a functional film layer with a high secondary electron emission coefficient is prepared on the inner wall of the channel through atomic layer deposition, and is used for reducing the influence of the material rear glass substrate on the gain characteristics. Compared with the prior art, the gain stability and working life of the microchannel plate prepared through the method are obviously improved, and the product consistency and reliability are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microchannel plate technology, and more specifically to a method for improving the gain stability of microchannel plates based on ion exchange. Background Technology

[0002] As the core electron multiplier device in super-second-generation image intensifiers, the performance of the microchannel plate (MCP) directly determines the tactical specifications of night vision equipment. The working principle of the MCP mainly relies on the secondary electron emission capability of the material on its channel wall. When an appropriate electric field is applied between the upper and lower metal electrodes of the MCP, incident charged particles (including photoelectrons, electrons, or ions) collide with the channel wall, triggering secondary electron emission. This process repeats along the channel axis under the influence of the electric field, generating an avalanche-like electron multiplication effect, ultimately outputting a significantly amplified secondary electron signal at the high potential end. Compared with traditional discrete electron multipliers, the MCP, with its unique two-dimensional array micropore structure (pore diameter 3-10 μm, pore spacing 5-15 μm), achieves high gain while also possessing sub-micron spatial resolution and picosecond time response characteristics. This allows night vision equipment systems to overcome size and weight limitations, meeting the lightweight requirements of individual soldier helmet-style equipment.

[0003] In the fabrication process of conventional microchannel plates (MCPs), the core step relies on glass multifiber drawing technology. This process uses lead silicate-coated glass tubes and matching core rods as starting materials, which are co-drawn into single composite fibers at high temperatures. Subsequently, through a series of processes including precise arrangement, multifiber drawing, array assembly, hot-melt pressing, slicing, rounding, precision grinding, chamfering, and polishing, a thin substrate with a dense array of microchannels is finally formed. This substrate needs to undergo further hydrogen reduction treatment to form a semiconductor layer with high secondary electron emission rate on the inner surface of its microchannels. The discovery of new problems and technologies brings new opportunities, but also new problems and challenges. The development of microchannel plates with high gain stability and long lifespan is a complex engineering project involving the coupling of multiple factors such as glass systems, complex structures, microstructures, and surface treatment technologies. The gain stability and reliability of MCPs during long-term operation are directly related to the stability of the alkali concentration (K, Na) on the material surface, which in turn depends on factors such as the type and concentration of the alkali.

[0004] Currently, the bottleneck technical problem of electron multiplication efficiency degradation in microchannel plates during long-term operation leads to unsatisfactory yield and stability of super-second-generation image intensifiers. Domestic and international research mainly focuses on how to improve the gain and reduce noise of MCPs in traditional lead-bismuth silicate glass microchannel plates. However, research on micro-nano scale processes such as secondary electron transport and decay within the microchannels has not been mentioned, and research on the stability, reliability, and related effects on the working life and control methods is almost non-existent. Summary of the Invention

[0005] To overcome the problems of existing technologies, this invention proposes a method for improving the gain stability of microchannel plates based on ion exchange. This method employs a combination of ion exchange and atomic layer deposition techniques, immersing a hydrogen-calcined MCP glass substrate in a molten salt solution (such as LiNO3 or AgNO3) to enhance the Kc content on the channel surface. + Na + With other cations in molten salt (such as Li) + Ag + Ion exchange occurs, significantly reducing the K and Na concentrations on the inner wall surface of the channel. Simultaneously, after the MCP sample undergoes the above-mentioned special steps, an atomic layer deposition layer with a high secondary electron emission coefficient (such as Al2O3 and MgO) is prepared on the inner wall of the channel. This layer is used to reduce the influence of the glass substrate behind the material on the gain characteristics, improving the gain stability and lifespan of the microchannel plate.

[0006] According to a first aspect of the present invention, a method for improving the gain stability of a microchannel plate based on ion exchange is proposed, comprising: The microchannel plate glass substrate after hydrogen burning is cleaned and vacuum degassing pretreatment is performed. The glass substrate has an effective working area and a solid edge surrounding the effective working area. The effective working area is a microchannel array structure with millions of channels and each channel has a pore size in the micrometer range. The pretreated microchannel plate glass substrate is placed in a molten salt solution and alkali metal ion exchange is carried out at high temperature to reduce the K and Na concentrations on the inner wall surface of the channel. The glass substrate after ion exchange is rinsed and dried. A secondary electron emission functional film was prepared on the inner wall of the channel after ion exchange using ALD deposition technology. After deposition, the material is annealed at high temperature in an O2 atmosphere to eliminate oxygen vacancies.

[0007] As an optional implementation, the mass percentage concentrations of K and Na elements on the inner wall of the channel of the glass substrate after ion exchange are both less than 0.1%.

[0008] As an optional implementation, the molten salt solution is a pure LiNO3 solution, and alkali metal ion exchange is carried out in an N2 atmosphere.

[0009] As an optional implementation, the molten salt solution is a mixed salt solution of AgNO3 and LiNO3, wherein AgNO3 is present in the mixed salt solution. + The mass percentage concentration is 5-10 wt%.

[0010] As an optional implementation, when performing alkali metal ion exchange using the AgNO3 and LiNO3 mixed salt solution, an Ar and H2 reducing atmosphere is used for protection to promote the formation of Ag nanoparticles on the channel surface.

[0011] As an optional approach, after alkali metal ion exchange using the AgNO3 / LiNO3 mixed salt solution, a post-treatment is also included before ALD deposition to remove surface Ag dendrites.

[0012] As an optional implementation, the post-processing includes: Heat treatment was performed at 280°C for 30 min under N2 atmosphere, followed by electrochemical polishing in 0.1M HNO3 solution at 10V for 2-10 min to eliminate surface Ag dendrites.

[0013] As an optional implementation, the material of the functional film layer is Al2O3 or MgO, and the uniformity of the functional film layer is better than or equal to 10%, and the film thickness is 10-30 nm.

[0014] As an optional implementation, the high-temperature annealing is rapid annealing with a heating rate greater than or equal to 50°C / s, used to induce preferred orientation of the MgO(200) crystal plane.

[0015] As an optional implementation, after ALD deposition, in-situ high-temperature annealing is performed in an O2 atmosphere to eliminate oxygen vacancies and improve the working life of the microchannel plate. The annealing temperature is 350°C (Al2O3 film), 450-480°C (MgO film), and the annealing time is 1-2 h.

[0016] In a second aspect of the present invention, a microchannel plate prepared according to the aforementioned method is provided.

[0017] In conventional processes, although functional thin films are deposited on the inner wall of the channel using ALD technology, the active alkali metal ions (K, Na) in the lead silicate glass substrate readily diffuse outward under the bombardment of the MCP high-voltage electric field and thermal effect, gradually penetrating and damaging the ALD film, leading to irreversible decay of the multiplication efficiency. In conjunction with the method of improving the gain stability and working life of the microchannel plate described in this invention, a molten salt ion exchange treatment is proposed after hydrogen burning and before ALD deposition, utilizing exogenous inactive ions (such as Li)... + Ag +The active free alkali metal source on the inner wall surface of the channel is replaced, which significantly reduces the residual mass percentage concentration of K and Na on the inner wall surface to below 0.1%. By cutting off the electrical degradation channel caused by alkali metal diffusion, a highly stable substrate structure is provided. Subsequently, an ALD film layer is deposited, thereby reducing the microscopic diffusion of alkali metal ions and significantly improving the gain stability of the microchannel plate.

[0018] Meanwhile, since the glass substrate has undergone hydrogen reduction (hydrogen burning process), a semiconductor conductive layer has been formed on the inner wall surface of the microchannel plate. Then, by using the present invention for rapid molten salt exchange, free alkali metals can be targetedly removed, the density and conformability of the thin film can be greatly improved, and the already formed conductive path will not be destroyed, thus ensuring the electrical performance and surface stability of the device.

[0019] The in-situ high-temperature annealing process after ALD deposition, driven by thermal activation, enables exogenous oxygen atoms to precisely fill oxygen vacancy defects inside the film and at the interface, suppressing thermionic emission and field emission during operation, reducing dark current and noise, significantly extending the working life of microchannel plates, and improving the consistency and reliability of MCP products.

[0020] Experimental test data show that traditional MCP samples without the method of this invention exhibit a precipitous drop in relative gain when the cumulative output charge reaches 30 coulombs (C), rapidly decreasing to less than 10% of the initial gain, resulting in extremely short device lifespan. In contrast, MCP samples treated with the process of this invention (ion exchange and ALD composite modification) show a very smooth gain decline curve with minimal fluctuations throughout the full charge output test over their entire lifespan. Even under extreme aging conditions with a cumulative output charge exceeding 200 coulombs (C), the relative gain can still be stably maintained at over 70% of the initial value, significantly improving the long-term operating life and stability of the device.

[0021] It should be understood that all combinations of the foregoing concepts and the additional concepts described in more detail below may be considered part of the inventive subject matter of this disclosure, provided that such concepts do not contradict each other. Furthermore, all combinations of the claimed subject matter are considered part of the inventive subject matter of this disclosure.

[0022] The foregoing and other aspects, embodiments, and features of the teachings of the present invention will be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the invention, such as features and / or beneficial effects of exemplary embodiments, will become apparent from the following description or may be learned through practice of specific embodiments according to the teachings of the present invention. Attached Figure Description

[0023] The accompanying drawings are not intended to be drawn to scale. In the drawings, each identical or nearly identical component shown in the various figures may be denoted by the same reference numeral. For clarity, not every component is labeled in each figure. Embodiments of various aspects of the invention will now be described by way of example and with reference to the accompanying drawings.

[0024] Figure 1 This is an XPS (X-ray photoelectron spectroscopy) image of the inner wall of a microchannel plate according to an embodiment of the present invention after ion exchange and ALD deposition.

[0025] Figure 2 The test curves show the gain stability of the MCP product obtained after ion exchange and ALD deposition of the inner wall of the microchannel plate of the present invention, compared with that of the conventional hydrogen-burning MCP product.

[0026] Figure 3 The test curves are for comparing the working life of the MCP products prepared in Examples 1 and 2 of this invention. Detailed Implementation

[0027] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.

[0028] Various aspects of the invention are described in this disclosure with reference to the accompanying drawings, which illustrate numerous illustrative embodiments. The embodiments of this disclosure are not necessarily intended to encompass all aspects of the invention. It should be understood that the various concepts and embodiments described above, as well as those described in more detail below, can be implemented in any of many ways, because the concepts and embodiments disclosed herein are not limited to any particular implementation. Furthermore, some aspects of the invention disclosed may be used alone or in any suitable combination with other aspects of the invention disclosed.

[0029] According to embodiments of the present invention, a method for improving the gain stability of microchannel plates based on ion exchange is proposed, comprising: The microchannel plate glass substrate after hydrogen burning is cleaned and vacuum degassing pretreatment is performed. The glass substrate has an effective working area and a solid edge surrounding the effective working area. The effective working area is a microchannel array structure with millions of channels and each channel has a pore size in the micrometer range. The pretreated microchannel plate glass substrate is placed in a molten salt solution and alkali metal ion exchange is carried out at high temperature to reduce the K and Na concentrations on the inner wall surface of the channel. The glass substrate after ion exchange is rinsed and dried. A secondary electron emission functional film was prepared on the inner wall of the channel after ion exchange using ALD deposition technology. After deposition, high-temperature annealing is performed to eliminate oxygen vacancies.

[0030] Therefore, the method of this invention overcomes the limitations of traditional methods that directly deposit thin films on the surface of multi-alkali glass. It introduces molten salt ion exchange treatment into the microchannel array structure obtained after the hydrogen reduction (hydrogenation) process, utilizing Li... + or Ag + Targeted replacement of active alkali metal ions (K) on the superficial layer of the inner wall of microchannels + Na + This process reduces the concentration of residual alkali metals on the surface of the channel inner wall to below 0.1%, eliminating the free alkali metal sources remaining on the surface of the channel inner wall of the glass substrate, and providing a substrate with extremely low surface alkali residue for subsequent coating. Then, it combines atomic layer deposition (ALD) technology to prepare a high secondary electron emission functional film layer (such as alumina Al2O3 or MgO), and finally eliminates oxygen vacancies through high-temperature annealing, blocking the degradation of electron multiplication efficiency at the microscale, and significantly improving the long-term gain stability, working life and product consistency of the microchannel plate.

[0031] As an optional implementation, the mass percentage concentrations of K and Na elements on the inner wall of the channel of the glass substrate after ion exchange are both better than 0.1%.

[0032] As an optional implementation, the molten salt solution is a pure LiNO3 solution, and alkali metal ion exchange is carried out in an N2 atmosphere.

[0033] As an optional implementation, the molten salt solution is a mixed salt solution of AgNO3 and LiNO3, wherein AgNO3 is present in the mixed salt solution. + The mass percentage concentration is 5-10 wt%.

[0034] As an optional implementation, when performing alkali metal ion exchange using the AgNO3 and LiNO3 mixed salt solution, an Ar and H2 reducing atmosphere is used for protection to promote the formation of Ag nanoparticles on the channel surface.

[0035] As an optional implementation, after alkali metal ion exchange using the AgNO3 and LiNO3 mixed salt solution, a post-treatment is further included before ALD deposition to remove surface Ag dendrites.

[0036] As an optional implementation, the post-processing includes: Heat treatment was performed at 280°C for 30 min under N2 atmosphere, followed by electrochemical polishing in 0.1M HNO3 solution at 10V for 2-10 min to eliminate surface Ag dendrites.

[0037] As an optional implementation, the material of the functional film layer is Al2O3 or MgO, and the uniformity of the functional film layer is better than or equal to 10%, and the film thickness is 10-30 nm.

[0038] As an optional implementation, the high-temperature annealing is rapid annealing with a heating rate greater than or equal to 50°C / s, used to induce preferred orientation of the MgO(200) crystal plane.

[0039] As an optional implementation, after ALD deposition, in-situ high-temperature annealing is performed in an O2 atmosphere to eliminate oxygen vacancies and improve the working life of the microchannel plate. The annealing temperature is 350°C (Al2O3 film), 450-480°C (MgO film), and the annealing time is 1-2 h.

[0040] It should be understood that in the traditional microchannel plate manufacturing process, Pb-containing glass materials are used as the core material and the outer material (the material composition is different). The process involves two stages of wire drawing (monofilament and multifilament), wire arrangement and rod assembly (rod assembly), high-temperature melting and pressing, cold processing, slicing and polishing (MCP blank), etching, hydrogen reduction, coating (functional film layer and metal electrode), and cleaning and testing.

[0041] The outer glass is typically made of lead silicate glass (containing PbO and Bi2O3), which is resistant to acid and alkali corrosion and possesses volume electrical resistance and secondary electron emission capability after hydrogen reduction, making it suitable for manufacturing high-precision hollow glass tubes. The core glass can be made of borosilicate soluble glass, whose coefficient of thermal expansion matches that of the outer glass, and can be completely corroded and removed by strong acids, making it suitable for manufacturing solid glass rods.

[0042] As an example, a solid core rod is coaxially inserted into a glass tube to form a concentric tube-rod composite. Then, monofilaments are drawn in a high-temperature drawing furnace, with the furnace temperature controlled within the glass softening range. An outer layer of corrosion-resistant glass wraps around the inner soluble core glass, resulting in a core-shell composite monofilament. This is cooled, wound, and cut into monofilaments of a fixed length. A second-stage drawing process is then performed, where a large number of monofilaments are neatly arranged in a tight hexagonal pattern and bundled into cylindrical rods. These rods are then fed into the drawing furnace for a second softening and stretching, resulting in a multifilament with a hexagonal cross-section. The multifilament contains hundreds of micro-monofilaments, which are fused and isolated from each other by the glass tube. After cooling, the multifilament is cut into short segments of the same height as the fusion mold. Then, the screen is assembled. Hexagonal multifilament segments are arranged tightly in hexagonal layers in a graphite mold, and frame glass material is placed around them. The mold is filled to form a complete square / circular blank. After the mold is put into the furnace, it is vacuum melted and pressed, heated to the glass softening point, and kept at the temperature to soften the surface of the multifilaments. At the same time, axial pressure is applied evenly, and all multifilaments and frames are fused together to form a whole dense glass blank rod.

[0043] After the glass preform cools, it is cold-processed and sliced ​​into thin sheets of the target thickness. These sheets are then ground and polished to obtain solid, non-porous MCP preform sheets (especially for circular glass substrates). Next, chemical core leaching is performed, immersing the MCP preform sheets individually or in groups using a fixture into a high-temperature mixed strong acid etching solution. This process dissolves only the soluble core glass, leaving the outer lead-resistant glass layer completely intact, forming a micron-level parallel microchannel array. Ultrasonic assistance can be used to assist in the etching process. Alternatively, a secondary, mild etching with a weak acid can be used to fine-tune the channel aperture, remove corrosion burrs from the channel walls, improve inner wall smoothness, and reduce dark noise.

[0044] Furthermore, the etched glass substrate sheet (containing millions of micrometer-level channels inside and surrounded by an unetched solid edge) is placed in a sealed quartz tube furnace. High vacuum is used to remove water vapor and impurities, and high-purity hydrogen is introduced. The temperature is raised to perform isothermal hydrogen reduction, and an ultrathin lead metal conductive layer is generated on the inner wall of the channel, while a high secondary electron emission interface is formed.

[0045] Then, a coating process is performed, such as depositing functional films (e.g., magnesium oxide, aluminum oxide, silicon oxide, etc.) on the inner wall and end face of the channel by ALD deposition, and depositing metal electrodes (Ni, Cr, Al alloy films) on the input and output surfaces at both ends. This yields the MCP finished product, which is then sorted and stored after final cleaning and performance testing.

[0046] In various embodiments of the present invention, the glass substrate used is an MCP blank that has undergone a hydrogen reduction process.

[0047] As an example, the process of a method for improving the gain stability and working life of microchannel plates based on ion exchange is as follows: steps 1-6.

[0048] Step 1: Pre-treat the microchannel plate glass substrate after hydrogen burning (i.e., the MCP blank after hydrogen reduction) by ultrasonic cleaning, drying and vacuum degassing.

[0049] As an example, the ultrasonic cleaning process is as follows: acetone for 15 min, ethanol for 15 min, and deionized water for 15 min; the frequency is 40 kHz and the power is 100 W.

[0050] The drying process was carried out at 100°C for 2 hours.

[0051] The vacuum degree of vacuum degassing is 10. -3 Pa, temperature 200°C, time 4 h.

[0052] Step 2: Place the pretreated glass substrate into the molten salt solution; wherein the molten salt solution formula is: LiNO3 (purity ≥99.5%) or AgNO3 / LiNO3 mixed salt (Ag +Concentration: 5-10 wt%) Step 3: Under high temperature conditions, react alkali metal ions (K) + Na + The exchange reaction is preferably carried out at a temperature above 300℃, especially 380℃±5℃, in an inert gas atmosphere (such as N2 flow, 50-80 sccm) for a time of more than 4 hours, preferably 4~8 hours (adjusted according to the channel diameter).

[0053] Step 4: Pre-treat the ion-exchanged glass substrate by rinsing, gradient cooling, and secondary drying.

[0054] The process involves rinsing with deionized water (resistivity ≥ 18 MΩ·cm) for 3 cycles, each lasting 10 minutes.

[0055] Gradient cooling rate: 2°C / min → room temperature, used to prevent thermal stress cracking.

[0056] Drying temperature: 120°C, vacuum degree: 10 -2 Pa, Time: 3 h.

[0057] Step 5: A secondary electron emission functional film layer is prepared on the inner wall of the ion-exchanged channel using ALD deposition technology. The film layer material can be Al2O3 or MgO. The specific process is as follows: For Al2O3 films: precursor TMA (trimethylaluminum Al(CH3)3) / H2O, pulse: 0.1 s / 0.05 s; MgO film: precursor Mg(Cp)2 (magnesium cyclopentadiene) / O3, pulse: 0.2 s / 0.1 s.

[0058] Deposition process parameter settings: Deposition temperature settings: 150-200°C (Al2O3), 250-300°C (MgO); Number of cycles: 100-500 cycles (film thickness 10-30 nm); Vacuum degree: 0.1-1 Torr; Purge time: 20 s (N2 flow rate: 50-60 sccm).

[0059] Step 6: After deposition, perform high-temperature in-situ annealing to eliminate oxygen vacancies and improve the working life of the microchannel plate. The annealing temperature is 350°C (Al2O3) and 450-480°C (MgO), and the time is 2 h.

[0060] {Example 1} Example 1 uses Li + Ion exchange (LiNO3 solution) + Al2O3 functional layer design.

[0061] Substrate specifications: lead silicate glass, 6 μm aperture, 0.3 mm thickness, aspect ratio 50:1. Specific process implementation is shown in the table below. XPS test results are as follows. Figure 1 As shown.

[0062]

[0063] like Figure 1 The elemental depth distribution energy spectrum of the inner wall of the microchannel plate shown, after ion exchange and ALD deposition, exhibits a strong characteristic peak of Al 2p, as shown in the image. Figure 1 The characteristic peaks of K and Na (such as Na 1s, K 2p) in the XPS spectrum shown are almost unobservable. The analysis results show that the surface mass percentage concentration is better than 0.1%, indicating that the active alkali metal ions in the shallow layer have been successfully removed by the molten salt ion exchange process.

[0064] {Example 2} Example 2 uses Ag + / Li + Mixed exchange (mixed salt solution) + MgO functional layer.

[0065] Substrate specifications: lead silicate glass, 6 μm aperture, 0.3 mm thickness, aspect ratio 50:1. Specific process implementation is shown in the table below. Test results for gain stability and operating life are as follows: Figure 2 and 3 As shown.

[0066]

[0067] Combination Figure 2 The diagram illustrates the relationship between operating voltage and gain (logarithmic scale), presenting the gain distribution and mean trends for two categories: Class A (ion-exchange based MCP) and Class B (traditional microchannel plates). Overall, as the operating voltage increases from 700V to 1000V, Class A (ion-exchange based microchannel plates) and Class B (traditional control) both show a continuous increase in gain, indicating that voltage is the core variable driving gain growth. The mean of Class A microchannel plates is consistently higher than that of Class B, reflecting the superior average gain performance of Class A under this operating condition. Considering the data dispersion characteristics, the mean deviation of Class A is relatively compact, with a narrower error bar (mean ± confidence interval), while Class B (dark blue scatter plots) shows slightly higher dispersion, indicating relatively weaker gain consistency.

[0068] exist Figure 3 The test comparison demonstrates the lifetime test results of improving the gain stability of microchannel plates (MCPs) based on ion exchange technology. The horizontal axis of the figure represents the cumulative output charge (C), and the vertical axis represents the relative gain. Figure 3(a) shows a conventional MCP sample not using the method of this invention, whose relative gain exhibits a sharp and significant decrease with increasing output charge, dropping to below 10% after 30 coulombs, indicating extremely rapid gain decay and poor stability. In contrast, Figure 3 (b) shows an MCP sample treated with a special process of ion exchange and atomic layer deposition of functional films on a hydrogen-burning substrate as proposed in this invention. Its gain decay curve becomes very flat, with minimal fluctuations throughout the entire cycle. This significant performance difference intuitively demonstrates that the method of this invention can effectively suppress the gain decay of MCPs, greatly improving device lifespan, product consistency, and reliability.

[0069] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.

Claims

1. A method for improving the gain stability of microchannel plates based on ion exchange, characterized in that, include: The microchannel plate glass substrate after hydrogen burning is cleaned and vacuum degassing pretreatment is performed. The glass substrate has an effective working area and a solid edge surrounding the effective working area. The effective working area is a microchannel array structure with millions of channels and each channel has a pore size in the micrometer range. The pretreated microchannel plate glass substrate is placed in a molten salt solution and alkali metal ion exchange is carried out at high temperature to reduce the K and Na concentrations on the inner wall surface of the channel. The glass substrate after ion exchange is rinsed and dried. A secondary electron emission functional film was prepared on the inner wall of the channel after ion exchange using ALD deposition technology. After deposition, high-temperature annealing is performed to eliminate oxygen vacancies.

2. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, After ion exchange, the mass percentage concentrations of K and Na elements on the inner wall of the channel of the glass substrate are both better than 0.1%.

3. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, The molten salt solution is a pure LiNO3 solution, and alkali metal ion exchange is carried out under an N2 atmosphere.

4. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, The molten salt solution is a mixed salt solution of AgNO3 and LiNO3, wherein Ag is present in the mixed salt. + The mass percentage concentration is 5-10 wt%.

5. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, When performing alkali metal ion exchange using the AgNO3 and LiNO3 mixed salt solution, a reducing atmosphere of Ar and H2 is used for protection to promote the formation of Ag nanoparticles on the channel surface.

6. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, After alkali metal ion exchange using the AgNO3 and LiNO3 mixed salt solution, a post-treatment is also included before ALD deposition to remove surface Ag dendrites.

7. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 6, characterized in that, The post-processing includes: Heat treatment was performed at 280°C for 30 min under N2 atmosphere, followed by electrochemical polishing in 0.1M HNO3 solution at 10V for 2-10 min to eliminate surface Ag dendrites.

8. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, The material of the functional film layer is Al2O3 or MgO, and the uniformity of the functional film layer is better than or equal to 10%, and the film thickness is 10-30 nm.

9. The method for improving the gain stability of microchannel plates based on ion exchange according to claim 1, characterized in that, The high-temperature annealing is rapid annealing with a heating rate greater than or equal to 50℃ / s, used to induce preferred orientation of the MgO(200) crystal plane.

10. A microchannel plate, characterized in that, It is prepared by the method of improving the gain stability of microchannel plates based on ion exchange as described in any one of claims 1 to 10.